The Use of Communication and Information Technology Innovation Among Micro, Small And Medium Enterprises (International Journal of Scientific Research and Management (IJSRM), 2018)
Innovation has significantly contributed to the transformation of organizations. The current research aims to determine the level innovation of communication and information technology that was employed by micro, small and medium sized corporations. The research respondents consisted of 100 micro, small and medium corporations, who were registered as active operated in the Industry, Trade and Cooperatives Office of Yogyakarta Municipality, Indonesia. The findings of this research demonstrated that micro, small and medium sized corporations innovated by employing communication and information technology in the operation of their businesses. The research discovered that 93% of the MSMEs (Micro, Small and Medium Enterprises) promoted their products using the internet, while 86% viewed innovation to be an important facet of their business. Furthermore, the smartphone was utilized by 100% of the MSMEs, to support the operations of their businesses.